Analysis of common carp Cyprinus carpio sperm motility and lipid composition using different in vitro temperatures - Dadras, Hadiseh; Sampels, Sabine; Golpour, Amin; Dzyuba, Viktoriya; Cosson, Jacky; Dzyuba, Borys (Animal reproduction science, 2017)
In fish, sperm quality is frequently associated with sperm motility variables. The response of sperm motility to different temperatures varies among species and plasma membrane lipid composition may contribute to variations in findings in previous research. In the present study, sperm motility and lipid composition were analysed between motile or immotile carp Cyprinus carpio sperm at different in vitro temperatures (4, 14 and 24°C). The duration of the period over which sperm motility is sustained was longer at 4°C compared with 14 and 24°C; while sperm velocity was greatest at 24°C. Motile sperm had lesser proportions of 18:3 (n-3) and 22:6 (n-3) fatty acids at 24°C relative to immotile sperm. There was no difference in fatty acid composition of motile and immotile sperm at 4 and 14°C. The total phospholipid content was less in motile than in immotile sperm at 24°C. At 24°C, phosphatidylcholine and phosphatidylserine proportions were less in motile than immotile sperm. It is concluded that lipid composition of motile carp sperm is affected by temperature, with greater temperatures associated with reduced lipid content, elevation of sperm curvilinear velocity and a decreased duration of the period over which motility is sustained.
Keywords: Carps; spermie; Temperature; Lipids; Male; lipidy; teplota; kapři; Animals; Spermatozoa; Sperm; mužské pohlaví; Motility; Sperm Motility; zvířata; motilita spermií